2013
DOI: 10.1371/journal.pone.0075481
|View full text |Cite|
|
Sign up to set email alerts
|

Tree Diversity Mediates the Distribution of Longhorn Beetles (Coleoptera: Cerambycidae) in a Changing Tropical Landscape (Southern Yunnan, SW China)

Abstract: Longhorn beetles (Coleoptera : Cerambycidae) have been used to identify sites of high biological diversity and conservation value in cultivated landscapes, but were rarely studied in changing landscapes of humid tropics. This study was conducted in a region of southern Yunnan, China, which was dominated by natural rainforest until 30 years ago, but is successively transformed into commercial rubber monoculture plantations since that time. The objectives were to investigate longhorn beetle species diversity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 39 publications
2
18
0
5
Order By: Relevance
“…Therefore, the recorded tendency of this group of species to move out of the forest might be induced by the additional resource requirements of adults. The lower number of species and individuals in the rubber plantation edge traps may indicate that rubber monocultures are not accepted as habitat, supporting the finding that longhorn beetle diversity in this tropical region is mediated by tree diversity (Meng et al 2013). In contrast, bark beetle distribution showed no significant difference between forest and rubber plantation edge traps, which might be explained by lower tree habitat quality requirements and higher dispersal ability.…”
Section: Discussionsupporting
confidence: 68%
“…Therefore, the recorded tendency of this group of species to move out of the forest might be induced by the additional resource requirements of adults. The lower number of species and individuals in the rubber plantation edge traps may indicate that rubber monocultures are not accepted as habitat, supporting the finding that longhorn beetle diversity in this tropical region is mediated by tree diversity (Meng et al 2013). In contrast, bark beetle distribution showed no significant difference between forest and rubber plantation edge traps, which might be explained by lower tree habitat quality requirements and higher dispersal ability.…”
Section: Discussionsupporting
confidence: 68%
“…Finally, Cerambycidae have potential as excellent bioindicators of forest 'health' due to their diversity, range of habitat specificities, and the multiple ecological roles they play, such as pollination, decomposition and as food for forest birds (Hanks 1999;Dajoz 2000). From a practical viewpoint, they can be relatively easy to identify, and there are already studies linking Cerambycidae diversity with floral diversity (Meng et al 2013) and biodiversity 'hot spots' (Holland 2007). Together with other recent papers proposing the use of Fijian invertebrates as bioindicators of habitat integrity and ecosystem 'health' (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Although many species of longhorn beetle live in a wide range of plants, some species live only in or on a certain host plant (Noerdjito 2011). Meng et al (2013) reported that there was a positive relationship between the number of longhorn beetle species and the number of tree species in a habitat. The diversity of trees reflected the availability of different types of dead wood.…”
Section: Discussionmentioning
confidence: 99%